Experimental study of solar powered ice maker using adsorption pair of activated carbon and methanol. (August 2018) - Attalla, M.; Sadek, S.; Salem Ahmed, M.; Shafie, Ibrahim M.; Hassan, M.
Highlights: Ice maker investigated experimentally by solar powered using adsorption pair. The Dubinin-Raduskevich (D-R) equation was used to compute pair characteristics. SAIMS is constructed and tested at real weather conditions of Qena city in Egypt. Acrylic sheets is used to enhance heat transfer and adsorbent temperature obtained. COPG is improved in comparison with single, double and TIM. Abstract: The present study introduces an experimental work for a solar adsorption ice maker system (SAIMS) using working pair of activated carbon (AquaSorb 2000) and methanol. The isotherm and isobar characteristics of the used pair are investigated by using Dubinin-Raduskevich (D-R) equation then, the SAIMS is constructed and tested at real weather conditions of Qena, Egypt. The findings of the pairs reveal that it suitable for the solar adsorption ice making applications with adsorption capacity found to be 0.6935 kg of methanol per kg of activated carbon (AquaSorb 2000). The constructed SAIMS can produce about 0.4 kg of ice per kg of AquaSorb 2000 by using the acrylic sheets in the adsorption bed instead of glass or other bed covers. Also, the experimental results proved that by using the acrylic sheets with a good design of the adsorption bed and due to the enhancement of heat transfer and high adsorbent temperature, the mass of desorbed methanol and produced ice is increased. Therefore, both gross and net COP are improved in comparison with other previous studies with single, double and Transparent Insulation Material (TIM) in the adsorber.